2008
DOI: 10.1007/s00590-008-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Revision total hip arthroplasty with cemented femoral component

Abstract: We reviewed retrospectively the results of 28 hips (25 patients) after revision of the femoral component with use of a cemented stem, because of aseptic loosening. The mean duration of follow-up was 4.43 years (range 2-12 years). Over the course of the study period, repeat revision was done in 4 hips after an average of 4.45 years. Three hips had a repeat revision of the femoral component because of aseptic loosening and one for a deep infection. The rate of loosening of the femoral component was 32.4% (9 hips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In registry studies, the survivorship of aseptic revision THA and 2nd stage reimplantation THA for PJI is best when intravenous antibiotics and antibiotic-loaded cement are used concurrently [ 7 ]. However, studies have shown that aseptic loosening rates of cemented revision THA are significant in the intermediate term [ [8] , [9] , [10] , [11] ]. Therefore, in most countries where the financial environment is suitable, cementless implants, which allow for biologic integration, are the preferred choice for aseptic revision and reimplantation THA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In registry studies, the survivorship of aseptic revision THA and 2nd stage reimplantation THA for PJI is best when intravenous antibiotics and antibiotic-loaded cement are used concurrently [ 7 ]. However, studies have shown that aseptic loosening rates of cemented revision THA are significant in the intermediate term [ [8] , [9] , [10] , [11] ]. Therefore, in most countries where the financial environment is suitable, cementless implants, which allow for biologic integration, are the preferred choice for aseptic revision and reimplantation THA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Technical advances in implant design and surgical techniques have improved survival but significant rates of loosening and bone loss have persisted. [4][5][6][7][8][9][10] Complications have also been associated with the use of uncemented femoral components, including subsidence 9,11 and proximal femoral fractures. 12 The variability of the endosteal geometry after removal of the femoral component can make proximal fit and fill difficult to achieve with an 'off the shelf' prosthesis.…”
mentioning
confidence: 99%